Metformin counteracts stimulatory effects induced by insulin in primary breast cancer cells - Domenica Scordamaglia; Francesca Cirillo; Marianna Talia; Maria Francesca Santolla; Damiano Cosimo Rigiracciolo; Lucia Muglia; Azzurra Zicarelli; Salvatore De Rosis; Francesca Giordano; Anna Maria Miglietta; Ernestina Marianna De Francesco; Veronica Vella; et al. (Journal of Translational Medicine, 2022)
Abstract Background Metabolic disorders are associated with increased incidence, aggressive phenotype and poor outcome of breast cancer (BC) patients. For instance, hyperinsulinemia is an independent risk factor for BC and the insulin/insulin receptor (IR) axis is involved in BC growth and metastasis. Of note, the anti-diabetic metformin may be considered in comprehensive therapeutic approaches in BC on the basis of its antiproliferative effects obtained in diverse pre-clinical and clinical studies. Methods Bioinformatics analysis were performed using the information provided by The Invasive Breast Cancer Cohort of The Cancer Genome Atlas (TCGA) project. The naturally immortalized BC cell line, named BCAHC-1, as well as cancer-associated fibroblasts (CAFs) derived from BC patients were used as model systems. In order to identify further mechanisms that characterize the anticancer action of metformin in BC, we performed gene expression and promoter studies as well as western blotting experiments. Moreover, cell cycle analysis, colony and spheroid formation, actin cytoskeleton reorganization, cell migration and matrigel drops evasion assays were carried out to provide novel insights on the anticancer properties of metformin. Results We first assessed that elevated expression and activation of IR correlate with a worse prognostic outcome in estrogen receptor (ER)-positive BC. Thereafter, we established that metformin inhibits the insulin/IR-mediated activation of transduction pathways, gene changes and proliferative responses in BCAHC-1 cells. Then, we found that metformin interferes with the insulin-induced expression of the metastatic gene CXC chemokine receptor 4 (CXCR4), which we found to be associated with poor disease-free survival in BC patients exhibiting high levels of IR. Next, we ascertained that metformin prevents a motile phenotype of BCAHC-1 cells triggered by the paracrine liaison between tumor cells and CAFs upon insulin activated CXCL12/CXCR4 axis. Conclusions Our findings provide novel mechanistic insights regarding the anti-proliferative and anti-migratory effects of metformin in both BC cells and important components of the tumor microenvironment like CAFs. Further investigations are warranted to corroborate the anticancer action of metformin on the tumor mass toward the assessment of more comprehensive strategies halting BC progression, in particular in patients exhibiting metabolic disorders and altered insulin/IR functions.